(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Damiri N, Rofiqi R, Mulawarnam, Rahim SE, Febyanti TP. 2021. Effect of three composts with active ingredients of Pseudomonas fluorescens on the development of white root disease and production of rubber plants. Biodiversitas 22: 3237-3242. White root disease (WRD) caused by Rigidoporus lignosus is a very dangerous disease and a scourge for rubber farmers because it can result in decreased production and kill rubber plants. This research was conducted to observe the impact of compost enriched with the biological agent Pseudomonas fluorescens on the development of white root disease and production in rubber plants. The results showed that the application of compost with active ingredient of P. fluorescens isolates A and B reduced the severity of white root disease in plants with mild, moderate and severe infections, 34.12%, 29.31% and 57.21% respectively. Application of compost with P. fluorescens isolates A and B, either singly or in combination, can increase latex production. The treatment of giving compost enriched with P. fluorescens isolates AR and ABR on rubber plants infected with mild WRD resulted in the highest latex production of 406 gm and 402.74 gm per plant, respectively. These two treatments did not differ from each other but were significantly different from the other treatments and controls.